The effect of opioid agonists and antagonists on gastrointestinal motility in mice selected for high and low swim stress‐induced analgesia. Issue 2 (28th October 2015) - Wasilewski, A.; Lesniak, A.; Bujalska‐Zadrozny, M.; Sadowski, B.; Fichna, J.; Sacharczuk, M.
Abstract: Background: The opioid system in the gastrointestinal (GI) tract plays an important physiological role, but is also responsible for the side effect of opioid drugs, including troublesome constipation in chronic pain treatment. The aim of this study was to characterize and validate a new mouse model to study the effects of opioid agonists and antagonists in the GI tract. Methods: Six‐week‐old male Swiss‐Webster mice, divergently bred for high (HA) and low (LA) swim stress‐induced analgesia (SSIA), were used in the study. To assess the influence of opioid agonists (morphine and loperamide) and antagonists (naloxone hydrochloride, NLX and naloxone methiodide, NLXM) on GI motility, whole GI transit (whole GIT) and upper GIT assays were conducted. To evaluate the expression of opioid receptors in the ileum and colon of HA and LA mice, immune staining was performed. Key Results: The effect of morphine was more pronounced in HA line, whereas loperamide exerted a stronger effect in LA mice. Furthermore, NLX and NLXM differentially abolished the inhibitory action of the central and peripheral opioid system on whole and upper GIT in HA and LA mice. The differences in GI motility between HA and LA mice coexisted with parallel changes in the expression of opioid receptors in the ileum and colon. Conclusions & Inferences: Differences in the activity of the endogenous opioid system are responsible for the vulnerability to changes in GI motility during treatment with opioids. Our findings validate the HA/LA model for further studies on opioids in the GI tract. Abstract : This study has been undertaken to assess the action of selected opioid agonists and antagonists in the gastrointestinal (GI) tract of Swiss‐Webster mice selectively bred toward high (HA) and low (LA) swim stress‐induced analgesia (SSIA). Selective breeding for high and low SSIA modifies the degree of opioid involvement in the neural mechanisms that control GI transit. The differences in GI motility between HA and LA mice coexisted with parallel changes in the expression of opioid receptors in the ileum and colon.